2012
DOI: 10.1186/1471-2458-12-1087
|View full text |Cite
|
Sign up to set email alerts
|

Differences between 9–11 year old British Pakistani and White British girls in physical activity and behavior during school recess

Abstract: BackgroundSchool recess provides an important opportunity for children to engage in physical activity. Previous studies indicate that children and adults of South Asian origin are less active than other ethnic groups in the United Kingdom, but have not investigated whether activity differs within the shared school environment. The aim of this study was to test the hypothesis that British Pakistani girls aged 9–11 years are less active during recess than White British girls.MethodsIn Study One, the proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…They found significant differences between the two ethnic groups for the average counts per minute overall and during break-time, with South Asians being less active during break-time [ 10 ]. Pollard et al 2012 examined differences in activity during break time in school, and found that British Pakistani girls were less active than White British children, which concurs with the findings from Eyre et al 2013 [ 25 ].…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…They found significant differences between the two ethnic groups for the average counts per minute overall and during break-time, with South Asians being less active during break-time [ 10 ]. Pollard et al 2012 examined differences in activity during break time in school, and found that British Pakistani girls were less active than White British children, which concurs with the findings from Eyre et al 2013 [ 25 ].…”
Section: Resultssupporting
confidence: 58%
“… Average counts/minute: White European: 481 South Asian: 452 [ 23 ] Owen et al 2009 9 to 10 London, Birmingham, Leicester Accelerometer worn for 7 days, during waking hours. Average counts/minute: Average counts/minute: Average counts/minute: White European: 498 White European: 537 White European: 463 South Asian: 457 South Asian: 510 South Asian: 414 Sedentary minutes/day: Sedentary minutes/day: Sedentary minutes/day: White European: 554 White European: 551 White European: 556 South Asian: 593 South Asian: 579 South Asian: 604 Moderate and vigorous minutes/day: Moderate and vigorous minutes/day: Moderate and vigorous minutes/day: White European: 70 White European: 77 White European: 62 South Asian: 65 South Asian: 73 South Asian: 57 Mean number of steps: Mean number of steps: Mean number of steps: White European: 10,220 White European: 10,882 White European: 9,660 South Asian: 9,314 South Asian: 10,202 South Asian: 8,571 [ 25 ] Pollard et al 2012 9 to 11 North East England Accelerometer worn for 2 school days Percentage of time sedentary during recess: White British: 54.5 % British Pakistani: 57.3 % Percentage of time in moderate and vigorous activity during recess: White British: 15.4 % British Pakistani: 12.9 % [ 9 ] Duncan et al 2012 8 to 11 Coventry Pedometers worn over 4 days Average weekday steps/day: ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other works also exist which are related to a different technique directly linked with play, System for Observing Children's Activity and Relationships, acronym SOCARP (Pollard, Hornby-Turner, Ghurbhurrun, & Ridgers, 2012;Powell, Woodfield, & Nevill, 2016;Ridgers, Fairclough, & Stratton, 2010 Ridgers, & Porteous, 2013;Woods, Graber, & Daum, 2012;Woods, Graber, Daum, & Gentry, 2015).…”
Section: Introductionmentioning
confidence: 99%